Implementation of Independent Character in Student Learning During the COVID-19 Period at Elementary School: Implementasi Karakter Mandiri Dalam Belajar Siswa Dimasa COVID-19 di SD - Karisma Tias Fadilah; Machful Indra Kurniawan (Academia Open, 2021)
The purpose of this study was to analyze how the process of applying independent character in student learning during the COVID-19 era at SDN Entalsewu. This study uses a descriptive qualitative approach. The source of data in this study is the theory of primary data obtained from the results of research that has been carried out by researchers in the field. Methods of data collection using observation, interviews and documentation. The results of this study indicate that the application of independent character in student learning goes well, although there are obstacles regarding the lack of consistency of parents.